Spontaneous somatic tetraploids in cassava - Hahn, S.K.; Bai, V.K.; Asiedu, Robert (1992)
One suspected mutant with the broad, thick and dark green leaves characteristic of tetraploid cassava was found from each of the cassava clones TMS 91934 and TMS 89/00037-17 planted out in the field. Cytological examination confirmed them as tetraploids with chromosomes number 2n=4x=72. The mutants seen to be derived from natural solid mutation of axillary or adventitious buds through somatic chromosomes doubling of the initial cells of the buds as a result of abnormal mitotic division. Somatic doubling seems to take place rather frequently in cassava compared to the other plant species. The tetraploid mutants inferior in vigour to their diploid mother clones but would be valuable as parents for improvement of cassava at tetraploid level as a complement to sexual polyploidization.